QUANTITATIVE ANALYSIS OF DEXTROMETHORPHAN-HBr, GUAIFENESIN AND DIPHENHYDRAMINE-HCl IN TABLET DOSAGE FORM BY SUCCESSIVE RATIO DERIVATIVE SPECTRA METHOD - TARIGAN, RIDA EVALINA; ANDRY, MUHAMMAD; DEWI, RATIH KUMALA; NASUTION, MUHAMMAD AMIN; LUBIS, MUHAMMAD FAUZAN (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aims to develop a spectrophotometric method with the successive ratio derivative spectra method using ethanol pro analysis solvent to obtain the results of the levels of Dextromethorphan (DEX) Hydrobromide (HBr), Guaifenesin (GUA) and, Diphenhydramine (DIF) Hydrochloric Acid (HCl) in tablet dosage form. Methods: This method is straightforward to determine the levels of DEX HBr, GUA, and DIF HCl in the wavelength range of 200-400 nm using absorption, which is calculated experimentally using spectrophotometry UV-Vis. Results: The maximum wavelengths of DEX HBr, GUA and DIF HCl were obtained at 278 nm, 273 nm, and 252 nm, respectively. The average % accuracy was obtained at 99.50% for DEX HBr, 99.91% for GUA, and 99.98% for DIF HCl in dosage forms. Conclusion: This method was successfully applied to determine the levels of DEX HBr, GUA and DIF HCl in tablet preparations and met the validation requirements.